A systematic review of re-detectable positive virus nucleic acid among COVID-19 patients in recovery phase (2020)
large number of coronavirus disease 2019 (COVID-19) patients have been cured and discharged due to timely and effective treatments. While some discharged patients have been found re-positive nucleic acid again in the recovery phase. Until now, there is still a great challenge to its infectivity and the specific potential mechanism which need further discussion. However, more intensive attention should be paid to the prognosis of the recovered patients. In this review, we mainly focus on the characteristics, potential reasons, infectivity, and outcomes of re-detectable positive patients, thereby providing some novel insights into the cognition of COVID-19.